Evaluation of White-rot Fungi for Biopulping of Wood - Kang, Kyu-Young (The Korean Society of Mycology, 2007)
Ergosterol involves in fungal cell growth as a major component in fungal cell membranes. It can be an indicator that shows the fungal activity, and its content depends on the fungal strains, culture, growth conditions and so on. In this study, fungal activities and growth patterns of three white-rot fungi strains isolated in Korea were evaluated by determination of ergosterol contents during the incubation. Wood decay test and chemical analyses of wood were also performed to verify the relationship between fungal activity and wood degrading capacity of white-rot fungi for 60 days. In the results of experiments, it is considered that the test strains selectively degrade large amount of lignin in wood at the early stage of decay. Especially, Phanerochaete chrysosporium showed the best capability on selective degradation of lignin among the test fungi. It is suggested that the determination of ergosterol content in the fungal culture during the incubation is the simple and effective screening method of white-rot fungi for the application to biopulping of wood.